2002
DOI: 10.1073/pnas.262438199
|View full text |Cite
|
Sign up to set email alerts
|

A unique molecular chaperone Cosmc required for activity of the mammalian core 1 β3-galactosyltransferase

Abstract: Human core 1 ␤3-galactosyltransferase (C1␤3Gal-T) generates the core 1 O-glycan Gal␤1-3GalNAc␣1-Ser͞Thr (T antigen), which is a precursor for many extended O-glycans in animal glycoproteins. We report here that C1␤3Gal-T activity requires expression of a molecular chaperone designated Cosmc (core 1 ␤3-Gal-T-specific molecular chaperone).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
423
1
10

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 441 publications
(446 citation statements)
references
References 33 publications
12
423
1
10
Order By: Relevance
“…Second, GnT-III may associate with some other molecules, which define the specificities for protein or peptide substrates. Several studies have shown that the glycosyltransferase complex formation may play a crucial role in the determination of both activity and substrate specificity [35,36]. Third, each glycosyltransferase may have its own pathway to operate glycosylation in Golgi apparatus.…”
Section: Roles Of N-glycosylation On α5β1 Integrinmentioning
confidence: 99%
“…Second, GnT-III may associate with some other molecules, which define the specificities for protein or peptide substrates. Several studies have shown that the glycosyltransferase complex formation may play a crucial role in the determination of both activity and substrate specificity [35,36]. Third, each glycosyltransferase may have its own pathway to operate glycosylation in Golgi apparatus.…”
Section: Roles Of N-glycosylation On α5β1 Integrinmentioning
confidence: 99%
“…For further elongation, T‐synthase (core 1 β1,3‐galactosyltransferase) is the key enzyme during the O‐glycosylation process 14. Interestingly, the expression and activity of T‐synthase require an endoplasmic reticulum(ER)‐resident molecular chaperone named Cosmc 15, 16, 17. Knockout of either T‐synthase or Cosmc in mice causes Tn expression in vivo 18, 19, 20.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, T‐synthase, Cosmc and C3GnT are essential for complete O‐glycosylation in colonic tissues. Accordingly, aberrant O‐glycosylation in colonic tissues, characterized by Tn antigen exposure, has been suggested to arise from disturbances in the expression and activity levels of T‐synthase, Cosmc and/or C3GnT 17, 22, 23, 24, 25. However, it is not known whether or how aberrant O‐glycosylation may contribute to the development and progression of CRC.…”
Section: Introductionmentioning
confidence: 99%
“…T-synthase (C1␤3Gal-T) forms a complex with core 1 ␤3GalT-specific molecular chaperone, which functions as a specific chaperone. Core 1 ␤3GalT-specific molecular chaperone is essential for the T-synthase activity and synthesizing T-antigen (42). Actually, core 1 ␤3GalT-specific molecular chaperone is a factor responsible for Tn syndrome, a genetic disease involving a deficiency in T-antigen but no defect in T-synthase (43).…”
Section: Discussionmentioning
confidence: 99%